A hypomorphic Il2rb mutant mouse model recapitulates and reveals mechanisms of human T cell immune dysregulation in IL-2Rβ deficiency - Berenice Cabrera-Martinez; Josselyn E. Garcia-Perez; Ryan M. Baxter; Victor G. Lui; Tusharkanti Ghosh; Ahmet Eken; Zander Kostka-Newman; John Rhey Mhar Garcia; Jeremy Rahkola; Rachel L. Gessner; Cullen M. Dutmer; Jared Klarquist; et al. (Cell Reports)
Summary: Here, we describe the use of a homologous knockin mouse model to further decipher the mechanism(s) of a novel human homozygous IL2RB hypomorphic mutation. Our model recapitulates the human immune dysregulation phenotype, showing decreased mutant interleukin-2Rβ (IL-2Rβ) cell-surface expression, impaired IL-2/15-dependent STAT5 signaling, elevated serum IL-2/15 levels, expanded effector memory CD8+ T cells, and severely reduced regulatory T cells (Tregs). Using mixed bone marrow chimeras (BMCs) and wild-type (WT) Treg transfers, we distinguish receptor-intrinsic from receptor-extrinsic immunopathogenesis. Both approaches suppress abnormal serum cytokine levels and autoimmunity without affecting endogenous mutant Tregs. Mutant animals receiving WT Tregs neonatally exhibit almost complete restoration of conventional T cell distribution, IL-2Rβ receptor surface expression, and STAT5 signal transduction, while BMC animals exhibit only partial restoration. Our findings demonstrate that CD8+ T cells and Tregs have distinct IL-2/15 ligand/receptor ratios and signaling thresholds required for proper development/function, revealing mechanistic insights applicable to immunotherapy for autoimmunity.